Methods Of Visualization Of Educational Materials In Teaching Russian To International Students - Mirzayeva .E.T (Genius Journals, 2023)
The article describes new trends in teaching foreign languages. The rapid development of new technologies makes it possible to actively apply various visualization techniques that contribute to maintaining motivation and stimulating cognitive interest of foreign students in the process of teaching the Russian language.
Keywords: digital technologies; visualization; cognitive interest